Karakteristik dan Corak Pemikiran Teologi Islam Klasik dan Modern - Zulkarnain Zulkarnain (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
Classical theology is a legacy from past theologies in the span of Islamic history and has apologetic characteristics (long debates on the area of mortal sin, eschatology, heaven and hell and the eternity of the Qur'an) and romantic remembers and longs for the greatness and excellence of past theologians without filling and preparing for global competition to be faced, while the style of modern theological thinking is to prioritize substance rather than form, and function Islamic values to overcome concrete community problems such as ignorance, poverty, unemployment, and social backwardness and develop science and science within the framework of prosperity and the peace of mankind on this earth. The two theological styles that exist in society make the color of the paradigm of Islamic theology must be able to be dialecticized by adherents of more moderate theology, so that abandoning classical theology does not mean leaving totality but changing the construct of thinking towards the substance of ijtihad in accordance with messages of humanist values.